Methylation and algorithms in biological aging: a scoping review - Ziesel, Alison; Reeves, Jennifer; Mallidou, Anastasia; Newton, Lorelei; Rhodes, Ryan E.; Zhang, Jie; Paterson, Theone; Jabbari, Hosna (Frontiers in Aging, 2025)
The role of DNA methylation in the process of biological aging is a particularly active area of research, where methylation changes may be a consequence or a driver in the deviation between biological and chronological age. We employ a scoping review strategy to analyze the results of 435 relevant research papers, 167 of which employed methylation-based strategies to interrogate biological age. Our work details the progression and refinement of these strategies over time, as well as the development of novel methylation-based clocks and algorithmic methods. Our chosen review strategy allows for the identification of research findings consistent and discordant with one another, as well as focusing on exciting, potential research areas regarding measurement, calculation, and assessment of epigenetic biological age.